The Effect of Online Customer Reviews on Purchase Intention With Customer Trust as A Variable in Purchase Decision on Sociolla Consumers - Tanuwijaya, Christina Kelly; Ellitan, Lena; Lukito, Robertus Sigit Haribowo (Program MM Universitas Surabaya, 2023)
Purpose: This study aims to analyze the effect of Online Customer Reviews on purchase intention with customer trust as a purchasing decision variable for Sociolla consumers. Method: This research is using the Non Probability Sampling method with Purposive Sampling. The sample used in this study was 250 respondents with characteristics; Men and women aged 17 years and over, know and have an account on the Sociolla website, and have also shopped at Sociolla in the last 3 months. Data was collected by distributing questionnaires and using the SEM-PLS Software 4.0 analysis technique for analysis. Results: The results of this study indicate that Online Customer Reviews has a positive influence on customer trust on the Sociolla website, customer trust has a positive influence on consumer buying interest to shop online, and Online Customer Reviews has a positive influence on consumer buying interest through customer trust to shop on line.